PENGGUNAAN MEDIA SOSIAL DALAM KAMPANYE POLITIK DAN DAMPAKNYA TERHADAP PARTISIPASI POLITIK DAN PERSEPSI PUBLIK - Ahmad Salman Farid (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2023)
In this increasingly advanced digital era, social media has become a powerful platform for sharing information, influencing opinion, and mobilizing the masses. Therefore, it is important to understand how the use of social media in political campaigns affects political participation and public perception. This study aims to investigate the effect of social media on political behavior, with a focus on the use of social media in political campaigns and its impact on political participation and public perception. This research will use a case study approach to analyze several political campaigns that involve social media as the main communication tool. Data will be collected through online surveys, interviews and analysis of social media content. Respondents who were sampled in this study were individuals involved in political campaigns using social media, as well as the general public who actively consume political content on social media. Based on this research, it can be concluded that the use of social media in political campaigns has a significant influence on political behavior, political participation and public perception.